Data migration in cloud computing using honey encryption - Ravindranadh, K; Sai Kiran, Mallarapu; Durga Sai Pavan Kumar, B; Priyanka, D (International Journal of Engineering and Technology, 2018)
Cloudcomputing provides variouskindsof servicesfor storingdata, load balancing betweencloudsandprovides an infrastructure for developing applicationsandmanaging them.Duetovariousattractive services provided by various cloudservice providers, users migrating their data from  their storage systemtocloudserviceprovider.Whilemigratingdatatoa cloudservice provider there will be  security  and privacy  protection concerns arises.Byconsideringthese concerns we are  proposing a secure privacy protection  migration usinghoney-encryptioncryptographicalgorithmfordata whichis outsourceddatatocloudandweareusingmigrationprotocolwhile migratingdatafromexisting serverstoragesystemtocloud server  storage systemwhichensures dataintegrityand data confidentiality.